(1277) Regional planning as a tool of strengthening the national economy التخطيط الإقليمي كأداة لتعزيز الاقتصاد الوطني - Sobhy, Hoda M. (The Institute Of National Planning., 2018)
The larger part of the theory of development planning has been developed without the inclusion of the element of space. The economy has been usually divided into sectors and within sectors projects, and methods of production have been studied, in addition fo obvious reasons, the element of the time plays an important part.